PROFESSIONAL DEONTOLOGY IN TEACHER TRAINING. REPORT ON A TRAINING EXPERIENCE - Fernando Sadio (Publicaciones, 2011)
This article presents the report of a pedagogical experience of Pre-Service Teacher Training on the subject of Professional Deontology, a curricular unit which is part of the degrees on Primary and Pre-School Education taught at Escola Superior de Educação do Instituto Politécnico de Coimbra (Portugal). The foundation of the curricular unit and its characteristics are presented, as well as the analysis of the students’ evaluation on its teaching effects as perceived by them. The analysis of the data, based on some contents of a portfolio, shows a considerable positive perception of those effects.